Morphology engineering of low-temperature-synthesized aluminum nitride - Han, Juyeon; Nayak, Kanhu Charan; Shim, Cheol-Hwee; Cha, Pil-Ryung; Choi, Hyunjoo; Ahn, Jae-Pyong; Lee, Kon-Bae (ELSEVIER, 2024)
We have developed an aluminum nitride (AlN) manufacturing method that operates below the melting point of aluminum. To examine the nucleation and growth mechanisms of AlN during the synthesis process, we used a variety of characterization techniques, including high-resolution transmission electron microscopy and rapid Fourier transform, which highlighted the development of its single-crystal and polycrystalline forms. The microstructural investigation showed that nitridation began with forming AlN shells on the surface of aluminum particles. Subsequently, volume nitridation occurred by transforming a single aluminum particle into either polycrystalline AlN with a columnar structure or single-crystal AlN. In addition, various interesting morphologies were observed during the microstructural investigation of low-temperature synthesized AlN, including truncated dodecahedrons, nanowires, particles, pillars, plates, and other polyhedral shapes. The study's microstructural findings provide crucial data on the AlN particle formation process, offering valuable insights expected to deepen understanding and expand the applications of AlN. Therefore, the consequence of this study is expected to make a meaningful contribution to understanding the formation mechanism of the particle type of AlN.